THE EFFECT OF SUPERVISION , WORK DISCIPLINE AND PHYSICAL ENVIRONMENT ON PERFORMANCE OF SIRNAJAYA VILLAGE GOVERNMENT EMPLOYEES - Sintia Arsita; Taufiq Rachman (SMBJ: Strategic Management Business Journal, 2022)
This study aims to determine the effect of supervision, discipline, and physical work environment at the Sirnajaya Village office, Serang Baru district. This research is population research that uses a saturated sample using a quantitative approach. The respondents were 61 officials from Sirnajaya Village, Serang Baru District. The place of research and the object of research, namely, the subject was an employee, and the object was the Sirnajaya Village Office. Based on the results of the t-count value in the t-table test, it is obtained that the Supervision variable (X1) partially has no significant effect and contributes negatively to employee performance in Sirnajaya Village. Work Discipline Variable (X2) partially has no significant effect and contributes positively to employee performance in Sirnajaya Village. Physical Environment Variables (X3) significantly and negatively contribute to employee performance in Sirnajaya Village.